The impact of attentional and emotional demands on memory performance in obsessive-compulsive disorder. (August 2017) - Fink, Jakob; Hendrikx, Friederike; Stierle, Christian; Stengler, Katarina; Jahn, Ina; Exner, Cornelia
Highlights: Experimentally induced divided attention deteriorated verbal memory performance. OCD-related thoughts were experimentally induced with a behavioral avoidance task. OCD-related thought monitoring deteriorated performance particularly in the OCD group. Personal involvement might further explain deteriorated memory performance in OCD. Abstract: Lower performance on memory tests in obsessive-compulsive disorder (OCD) has been repeatedly observed. However, the origins of these performance deficits are not sufficiently explained. In this study we tested if OCD-related extensive focus of attention on thoughts (heightened self-consciousness) could be an explanatory mechanism for lower memory performance. Heightened situational self-consciousness was manipulated by instructing participants to either monitor neutral thoughts or to monitor OCD-related thoughts. We included a Behavioral Avoidance Task based on individual obsessions and compulsions to induce OCD-related thoughts. Participants were asked to perform these monitoring tasks in parallel to a taxing verbal memory task, resulting in learning under divided attention. The two conditions of learning under divided attention were compared to a single-task condition. Twenty-four participants with OCD and 24 healthy controls took part in these three learning conditions. The results indicate that in both groups memory performance deteriorated in the two conditions with divided attention compared to the single task condition. In the OCD-related thought monitoring condition (OTM) self-consciousness and Behavioral Avoidance Task-induced stress and fear were particularly increased and memory performance further deteriorated in the OCD group. This finding highlights an important and underestimated mechanism (personal involvement) which might serve to better understand lower memory performance in OCD.